(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores innovative strategies in Teaching English to Speakers of Other Languages (TESOL), focusing on their impact on language acquisition and classroom engagement. By analyzing task-based learning, technology integration, and culturally responsive teaching, this research provides insights into their efficacy and applicability in diverse educational contexts. Findings suggest that these strategies foster a more inclusive, interactive, and effective learning environment.